Homecoming: finding a place for shamanic practice in the creation of post colonial theatre - Kiel, Sue (Department of Drama, 2015)
At the centre of my research, in the light of my homecoming and notions of home, there is a question: might I find a place where dimensions of shamanism might intersect with modes of performance, in the creation of theatre for the 21st Century? In this liminal hybrid moment, a place between the present and the future, I suggest that art is actually necessary and that it is essential for artists to build a counter-narrative, both locally and globally, to terror, suffering and denial. Art and social change can be a trend for certain nations, societies, even artists and theorists. In my view, however, which is my point of departure, it is particularly in an era of self reference, modernity, post modern and post colonial rupture and fragmentation that an informed coherence between the inexplicable terror of unsettling major social upheaval and the individual, may be able to be sketched once again and with certainty, by and through art and performance; if not actual transformation; then a witnessing, an acknowledgement and an end to the pain of denial. This explication begins with an overview of current socio-political dilemmas, and looks at the role of theatre in impacting change. My exploration continues with an examination of the role of shamanism as a tool to assist the theatre maker, the actor and even the audience in the pursuit of a transforming experience where one might initiate a shift in perceptions, thought and consciousness. In my observation of current theatre makers in South Africa, I am finding that this is already taking place. The object of this paper is to frame and make more specific, the role of shamanism as it connects to interdisciplinary techniques and technologies for performance. In my practical research, which will include my culminating production, Passages (provisional title), I attempt to tease out these methodologies in order to expand my work and be a part of the development of theory and practice in theatre making in these significant and urgent times, for my 21st Century homes. The primary theorists that I have referenced, contained in my theoretical framework, are Ashraf Jamal, Sarah Nuttall, Achille Mbembe, Homi Bhabha, Breyten Breytenbach, Iain Chambers and Hamid Naficy. In my research for my praxis, I have worked predominantly with the findings of Richard Schechner, Victor Turner, Antonin Artaud, Peter Sellars, Jerzy Grotowski, Alison Oddey and Rachel Karafistan.